Análise crítica dos potenciais impactos ambientais derivados das alterações do código florestal brasileiro em 2012 - Vargas, Fábio Alves de (2018)
Since the edition of the new forestall code of Brazil, Law n° 12.651/12, and due to its proposal as a bill, it was verificated that the proposals of changes, have influenced in scientific and academic aspects, and inclusive in public opinion, have been many debates allow to a suppose back over in effectiveness of protection of environment, evaluated by the Federal Constitution of 1988. This controvertial in right, the forestall code is being discussed since many years ago by the National Congress and in that context, rural people and environmentalists, have mantained a really battle. To now have prevailed the delinquency in effectuation of that changes and the game of interests and intentions. Thus, this dissertation, analyses the elements of the debate and the critics done by scientists allow of the principal changes occurred in the forestall Code of Brazil and of its real and possible consequences. Considering the multidisciplinarity of this theme, we realize a bibliographic investigation, respect to analyses, comparison and synthesis of knowledge already produced and publicated by the students of the forestall code and its changes. Therefore, the legislation have been analysed, considering the principal changes related to the forestall code of 1965 (4.771/1965); the direct imposed actions of unconstitutionality (ADIs); the critics to the changes; as well as the actual state of art in relation to the fulfilment of the actual legislation. By this analyses; we looked for also identifying sectors and subjects that defended the realized changes, considering also these arguments; as well as sectors and subjects against these changes. Though, the results obtained in this dissertation, allow to affirm that those legislative changes, undoubtly bring adverse impacts to environment and consequently to society. Some of them is the forestall generalized decrease and of other habitats; the weakness of the recuperation of essential ecologic processes; the compromisse and the integrity of atributes in permanent Preservation areas and the legal reserves; and the relativation to the duty of repair environmental damages. In spite of the existence of direct actions of inconstitutionalities, questioning some principles of the actual Forest Code, that were judged in february 28th of 2018, by the Supreme Federal Court, it results that the petitions had been judged partially proccessable. Another constatation of this investigation, indicates respect to delinquency in efectiveness of important instruments of the new law, as well as the formalization of the rural environmental indicators (CAR) and especially the elaboration and fullfilment of the programs of environmental regularization (PRA), given that, until now, there is not a definitive reglamentation. It concludes that the changes made by the law nº 12.651/12 and the absence of aplication of the law until now, had contributed to the intensification of decoupling in Brazil, especially in the amazonía. Also, delinquency in the aplication of the new law seems to be something, premeditated and orchestrated, given that instead of generate solutions and warrant an aplication of legal exigences, it is observed a process of breach of the legislation, add to the existence of gaps that have allowed different interpretations.